Incidence of late severe intestinal complications after bowel atresia/stenosis. Issue 1 (13th July 2022) - Hosokawa, Takahiro; Tanami, Yutaka; Sato, Yumiko; Ishimaru, Tetsuya; Kawashima, Hiroshi; Oguma, Eiji
Abstract: Background: To determine the incidence and risk factors for late severe intestinal complications after surgical repair for intra‐abdominal congenital intestinal atresia/stenosis. Methods: We included 51 patients who underwent surgical repair for congenital intestinal atresia/stenosis. Late severe intestinal complications included adhesive ileus, incisional hernia, or volvulus. Whether surgical intervention was urgent or not was recorded. The location of the atresia/stenosis was classified into two groups: atresia/stenosis located at the oral or anal side from the Treitz ligament. The type of atresia/stenosis was classified as low‐risk types (type I, mucosal web/II, fibrous cord/IIIa, mesenteric gap defect) and high‐risk types (IIIb, apple peel/IV, multiple atresia). We compared the incidence of late intestinal complications between the location of intestinal atresia/stenosis at the oral and anal side of Treitz ligament, and between low‐ and high‐risk types of atresia/stenosis using Fisher's exact test. Results: Eight (15.7%) had late intestinal complications, all of which occurred in patients with intestinal atresia/stenosis located on the anal side of the ligament of Treitz. Urgent surgical intervention was needed in four cases. There was a significant difference in the location of atresia/stenosis (with vs. without late intestinal complications at oral/anal side of the Treitz ligament: 0/8 vs. 24/19; P  = 0.005) and the type of intestinal atresia/stenosis (with vs. without that accompanying low‐/high‐risk type: 5/3 vs. 41/2; P  = 0.023). Conclusions: Physicians should consider the presence of intestinal complications that require surgical intervention in patients undergoing surgical reconstruction for jejunal and ileal atresia/stenosis with abdominal symptoms.